Establecer líneas de acción para la gestión integral de residuos sólidos domiciliarios de la ciudad de el Eslabón, provincia de Huallaga - Pereira Panduro, Cario Magno (2014)
This final report of the thesis implemented in the Eslabon district, describes the activities carried out in compliance with the stated objectives. The thesis entitled "ESTABLISH LINES OF ACTION FOR THE INTEGRAL MANAGEMENT OF RESIDENTIAL SOLIO WASTE OF THE ESLABON CITY, PROVINCE OF HUALLAGA, 2013 ", aims; determine the generation and physical composition of the salid waste, diagnose the current situation of the Integral Management of salid waste and propase alternative lines of action of work for proper handling, disposal and utilization of salid waste in the district of the link. With the implementation of the thesis is reached the following conclusions: ./ Per Capita Generation of Salid Waste - GPC in the Eslabon district is 0.58 kg/hab/day, which is to say that the projection of the salid waste generation in the Eslabon district will be a function of the population and this rate determined in the present study, a total of 1 ,855 ton/day . ./ The density of residential salid waste is 216,497 kg/m3 , the use of this value is important in designing a program of home salid waste containerization . ./ The physical composition of the residential salid waste is composed of · exploitable that represents the 86.25 %, waste not exploitable the 13.65 % of hazardous waste and the 0.1 O %. That the current situation of the Eslabon District, not counting with instruments that allow to perform an adequate Integral Management of Municipal Salid Waste is like that in many parts of the country disturbing because it demonstrates the lack of a system to regulate Salid Waste Management in the Eslabon district. Raise the lines of action of the Comprehensive Plan of Salid Waste in the district of the link, which is based on the following three key objectives: • Training, and advocacy with public authorities, to ensure that the recyclable material does not reach the landfill. • lnclusion of the recyclers in the chain of recycling, and in the system of integrated salid waste management. • Civil Raising awareness on the importance of managing adequately the salid residues promoting a "Environmental Citizenship ". For this you could say that it has complied with the stated objectives, for what it is recommended to get a copy to the District Municipality of the link to be taken into account, and with this accomplished a proper lntegrated Solid Waste Management. Key words: solid waste, proper handling.